Polar mesosphere summer echoes: a comparison of simultaneous observations at three wavelengths - Belova, E.; Dalin, P.; Kirkwood, S. (CCSD, 2008)
International audience On 5 July 2005, simultaneous observations of Polar Mesosphere Summer Echoes (PMSE) were made using the EISCAT VHF (224 MHz) and UHF (933 MHz) radars located near Tromsø, Norway and the ALWIN VHF radar (53.5 MHz) situated on Andøya, 120 km SW of the EISCAT site. During the short interval from 12:20 UT until 12:26 UT strong echoes at about 84 km altitude were detected with all three radars. The radar volume reflectivities were found to be 4×10 ?13 m ?1 , 1.5×10 ?14 m ?1 and 1.5×10 ?18 m ?1 for the ALWIN, EISCAT-VHF and UHF radars, respectively. We have calculated the reflectivity ratios for each pair of radars and have compared them to ratios obtained from the turbulence-theory model proposed by Hill (1978a). We have tested different values of the turbulent energy dissipation rate ? and Schmidt number S c , which are free parameters in the model, to try to fit theoretical reflectivity ratios to the experimental ones. No single combination of the parameters ? and S c could be found to give a good fit. Spectral widths for the EISCAT radars were estimated from the spectra computed from the autocorrelation functions obtained in the experiment. After correction for beam-width broadening, the spectral widths are about 4 m/s for the EISCAT-VHF and 1.5?2 m/s for the UHF radar. However, according to the turbulence theory, the spectral widths in m/s should be the same for both radars. We also tested an incoherent scatter (IS) model developed by Cho et al. (1998), which takes into account the presence of charged aerosols/dust at the summer mesopause. It required very different sizes of particles for the EISCAT-VHF and UHF cases, to be able to fit the experimental spectra with model spectra. This implies that the IS model cannot explain PMSE spectra, at least not for monodisperse distributions of particles.